Narratives from North Africa : South African prisoner-of-war experience following the fall of Tobruk, June 1942 (Historia, 2021)
This article aims to present to the reader previously unknown narratives of former prisoners of war (POWs) immediately following the fall of Tobruk in June 1942. The intention is not to explain the events that led to the fall of Tobruk or to lay blame with any specific leader or Allied nation involved in the Western Desert Campaign. The focus is rather on the events during and following the battle, specifically the experiences of the South Africans who were captured and became prisoners of war. Of the 33 000 Allied soldiers captured on 21 June 1942, 10 722 were South Africans who were all part of the 2nd South African Infantry Division under command of Major General H.B. Klopper. Making use of oral testimony, published and unpublished personal memoirs, as well as post-war statements found in the Department of Defence Archives and in the Ditsong National Museum of Military History, the article hopes to portray events as experienced by the ordinary rank and file men, giving a different perspective from that usually portrayed in military history publications which for the most part focus on the perspectives of those in command. Through this approach it should also become possible to extract the individual experience from the general experience, as each of the former POWs understood and interpreted what was happening to them in unique ways.
Keywords: North Africa; South Africa; Tobruk; June; 1942; prisoners of war (POWs)